Treatment of migraine in children and adolescents. The state of the art - Arruda, Renato; Arruda, Marco Antônio (Headache Medicine, 2023)
Introduction Headaches and migraine are common in the pediatric population, being one of the most frequent symptoms reported in practice. Additionally, it is a considerably disabling condition, which brings significant burden and impairs several aspects of a child or adolescent's life, such as mental and physical health, executive functioning, school performance. Children and adolescents with migraine have higher risk of psychiatric comorbidities and psychosocial adjustment difficulties, which, in turn, compromise even more patient's well-functioning. Objective The present article provides the clinician with a straightforward and evidence-based approach to migraine treatment in this age group. Comment Treatment of migraine in children and adolescents requires a systematic and thorough approach. Clinicians should keep in mind the important burden migraine brings to a child's life, thus investigate, and properly manage comorbidities presented. Patient and parents' education is a meaningful part of the treatment. Moreover, non-pharmacological treatments, such as healthy lifestyle habits, behavioral interventions may also play beneficial roles. When preventive treatment is indicated, it should be tailored considering drug's profile of effectiveness and safety, as well as patient's comorbidities. Lack of evidence in this context must not translate in lack of action by the clinician, since there may be a relevant burden associated. Therefore, reasoning for the perspicacious clinician is of fundamental importance and may influence positively the outcomes.